Women, murder, and equity in early modern England - Martin, Randall, 1958- (New York ; London : Routledge, 2008)
This book presents the first comprehensive study of over 120 printed news reports of murders and infanticides committed by early modern women. It offers an interdisciplinary analysis of female homicide in post-Reformation news formats ranging from ballads to newspapers. Individual cases are illuminated in relation to changing legal, religious, and political contexts, as well as the dynamic growth of commercial crime-news and readership.
Introduction -- Equity and self-defense in female homicide news -- Confession, conversion, and tactical resistance -- Women and poison -- Changing representations of infanticide and child murder -- Conclusion.
Includes bibliographical references (pages 241-271) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Women murderers -- England -- History -- 16th century; Murder -- England -- History -- 16th century; Meurtrières -- Angleterre -- Histoire -- 16e siècle.; TRUE CRIME -- General; Murder; Women murderers; England; Mörderin; England; 1500-1599; Geschichte 1600-1700.; Electronic books; History